Răspuns :
a) [tex]\it ~^{\sqrt{3}) } \frac{3}{\sqrt{3} } = \frac{ \not 3\sqrt{3} }{\not 3} = \sqrt{3}[/tex]
b) [tex]\it \frac{6}{\sqrt{18} } = ~^{\sqrt{2} )} \frac{6}{3\sqrt{2} } = \frac{6\sqrt{2} }{3 \cdot 2} = \frac{ \not 6\sqrt{2} }{\not 6} = \sqrt{2}[/tex]
c) [tex]\it \frac{\sqrt{27} }{6\sqrt{2} } = \frac{3\sqrt{3} }{6\sqrt{2} } = ~^{\sqrt{2} )} \frac{\sqrt{3} }{2\sqrt{2} } = \frac{\sqrt{6} }{2 \cdot 2} = \frac{\sqrt{6} }{4}[/tex]
j) [tex]\it - ~^{\sqrt{3}) } \frac{12}{\sqrt{3} } = -\frac{12\sqrt{3} }{3 } = -4\sqrt{3}[/tex]
k) [tex]-\frac{3}{\sqrt{27} } = - \frac{\not 3}{\not 3\sqrt{3} } = -~^{\sqrt{3}) } \frac{1}{\sqrt{3} } = \frac{\sqrt{3} }{3}[/tex]
l) [tex]\it \frac{2\sqrt{3} }{\sqrt{8} } = \frac{\not 2\sqrt{3} }{\not 2\sqrt{2} } = ~^{\sqrt{2}) } \frac{\sqrt{3} }{\sqrt{2} } = \frac{\sqrt{6} }{2}[/tex]
o) [tex]\it \frac{a\sqrt{b} }{b\sqrt{a} } \cdot \frac{\sqrt{a} }{\sqrt{a} } = \frac{a\sqrt{b} \cdot \sqrt{a} }{b\sqrt{a} \cdot \sqrt{a} } = \frac{a\sqrt{ab} }{b \cdot a} =\frac{\sqrt{ab} }{b}[/tex]